Effect of The Aqueous Extract of Rocket( Eruca sativa L.) Leaves on the Histological Structure of Some Organs in Male Mice (Journal of the College of Basic Education, 2022)
In this study we have assessed the effect of the hot aqueous extract of (Eruca sativa) leaves on the histological structure of (Kidney, liver and spleen) in male albino mice. Two experimental groups were used in this study(250 and 500mg/kg body weight).The extract was given orally for 30 days. There was a significant increase in weighs of the liver for the two treated groups as compared with control and only the 500mg/kg group shows a significant increase in weighs of kidney. The histological study for the treated groups shows hypertrophy of the hepatic cells with the accumulation of glycoprotein granules. Sections of the spleen revealed expansion of the white pulp and red pulp areas in addition to the presence of megakaryocytes and haemosedirosis in some areas. While sections of the kidney did not show a remarkable changes. A detection for some active ingredients found in the plant extract reveals the presence of (saponins ,alkaloids,flavenoids, tannins and glycosides).